2005
DOI: 10.1158/1055-9965.epi-05-0379
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Second Primary Cancer and Death Following a Diagnosis of Nonmelanoma Skin Cancer

Abstract: Cancer-free patients diagnosed with a first primary nonmelanoma skin cancer (NMSC) offer an opportunity for studying the risk of a second primary cancer without the confounding effect of systemic treatment. The objective of the study was to estimate the risk of second primary cancer in people with a history of basal cell carcinoma (BCC) or squamous cell carcinoma (SCC) and the risk of dying in cancer patients with a NMSC history. BCC and SCC cases diagnosed between 1956 and 2000 in Manitoba, Canada were follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
56
3
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(72 citation statements)
references
References 25 publications
11
56
3
2
Order By: Relevance
“…reports, except that the risk estimate tended to be lower in the present study (multivariable-adjusted HR ¼ 2.22) than those reported in previous case-control or registry-based studies (HR/ meta-analysis relative risk > 2.70) (6)(7)(8) and in a prospective study with a total of 19 174 individuals and a 16-year follow-up (multivariable-adjusted relative risk ¼ 7.94) (9). The modest associations reported in our study may be partly explained by the adjustment for a number of potential risk factors.…”
Section: Articlecontrasting
confidence: 87%
“…reports, except that the risk estimate tended to be lower in the present study (multivariable-adjusted HR ¼ 2.22) than those reported in previous case-control or registry-based studies (HR/ meta-analysis relative risk > 2.70) (6)(7)(8) and in a prospective study with a total of 19 174 individuals and a 16-year follow-up (multivariable-adjusted relative risk ¼ 7.94) (9). The modest associations reported in our study may be partly explained by the adjustment for a number of potential risk factors.…”
Section: Articlecontrasting
confidence: 87%
“…Therefore, patients with these characteristics are expected to have a higher Vitamin D status and possibly a lower risk of certain second cancers. [2][3][4][5]9 Indeed, similar to previous studies, 2-4,10 Levi et al found lower SIR point estimates for SCC and basal cell carcinoma (BCC) than for melanoma, although no decreased risks were observed. After stratification by location and subtype of skin cancer, neither Levi et al…”
Section: Stratificationssupporting
confidence: 66%
“…2,3 and Nugent et al 4 Most other studies obtained similar results to the findings of Levi et al This might be because skin cancer patients do not have higher vitamin D levels or because vitamin D does not protect against the development of second tumors. However, any decreased or an increased risk might also be obscured by some methodological issues, that are illustrated later.…”
mentioning
confidence: 61%
“…As the numbers of cancer survivors and of older people increases, the occurrence of multiple primary cancers is also likely to increase [64][65][66][67][68]. Approximately one-third of cancer survivors aged >60 years were diagnosed more than once with another cancer.…”
Section: The Hypothesis Of Genome Intrusionmentioning
confidence: 99%